Pristane modulates specific changes on T cell dependent pathway of lupus in non-F1 BALB/c mice - Indriyanti, Niken; Arifianti, Lusiana; Soeroso, Joewono; Khotib, Junaidi (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Animal modeling for lupus is a crucial step in the process of discovering efficacious drugs. There are many drug candidates that have potential benefits for the treatment of lupus, but finding an appropriate model remains challenging. The appropriate model based on the literature is an induction model that uses 2,6,10,14 tetramethylpentadecane (TMPD) in female Balb/c mice. The TMPD increases the probability of damage beyond lupus, to the joint and kidneys. Therefore, the purpose of this study was to develop a lupus model by TMPD to test a drug candidate. The experimental method was measuring many biomarkers involved in the TMPD mechanism to obtain lupus-like disease mice. We measured CD4+CD25+FOXP3+ and CD4+CD62L+ T-regs, CD123+IFN-?+ dendritic cells (flow cytometry); total leukocytes (Turk staining); anti-Sm antibody (ELISA); and renal and joint histology (HE staining). After the 6th month, there were reduction (p<0.05) of the T regulatory percentage of CD4+CD25L+ T cells (Naïve=19.39±3.06%, TMPD-treated=5.72±3.43%) and CD25+FOXP3 + T cells (Naïve=10.32±4.47%, TMPD-treated=7.70±4.47%), meanwhile, the IFN-? increased significantly (p<0.05), (Naïve=6.92±8.67%, TMPD-treated=11.42±0.95%), and the total leukocytes increased (p<0.05) (Naïve=9,800±1,698, TMPD-treated=17,500±1,490 cells/mm3). The anti-Sm antibody was also present in the TMPD-treated mice as one cause which led to renal and joint structural disorders. The biomarkers were analyzed by using Independent T-test, so this positive lupus model with its tested biomarkers is valid and can be used to test drugs for lupus.